Observer Agreement on Computed Tomography Perfusion Imaging in Acute Ischemic Stroke. Issue 11 (November 2019) - El-Tawil, Salwa; Mair, Grant; Huang, Xuya; Sakka, Eleni; Palmer, Jeb; Ford, Ian; Kalra, Lalit; Wardlaw, Joanna; Muir, Keith W.; Adami, Alessandro; Cerase, Alfonso; Garcia, Ana; et al.
Abstract : Background and Purpose—: Computed tomography (CT) perfusion (CTP) provides potentially valuable information to guide treatment decisions in acute stroke. Assessment of interobserver reliability of CTP has, however, been limited to small, mostly single center studies. We performed a large, internet-based study to assess observer reliability of CTP interpretation in acute stroke. Methods—: We selected 24 cases from the IST-3 (Third International Stroke Trial), ATTEST (Alteplase Versus Tenecteplase for Thrombolysis After Ischaemic Stroke), and POSH (Post Stroke Hyperglycaemia) studies to illustrate various perfusion abnormalities. For each case, observers were presented with noncontrast CT, maps of cerebral blood volume, cerebral blood flow, mean transit time, delay time, and thresholded penumbra maps (dichotomized into penumbra and core), together with a short clinical vignette. Observers used a structured questionnaire to record presence of perfusion deficit, its extent compared with ischemic changes on noncontrast CT, and an Alberta Stroke Program Early CT Score for noncontrast CT and CTP. All images were viewed, and responses were collected online. We assessed observer agreement with Krippendorff-α. Intraobserver agreement was assessed by inviting observers who reviewed all scans for a repeat review of 6 scans. Results—: Fifty seven observers contributed to the study, with 27 observers reviewing all 24 scans and 17 observers contributing repeat readings. Interobserver agreement was good to excellent for all CTP. Agreement was higher for perfusion maps compared with noncontrast CT and was higher for mean transit time, delay time, and penumbra map (Krippendorff-α =0.77, 0.79, and 0.81, respectively) compared with cerebral blood volume and cerebral blood flow (Krippendorff-α =0.69 and 0.62, respectively). Intraobserver agreement was fair to substantial in the majority of readers (Krippendorff-α ranged from 0.29 to 0.80). Conclusions—: There are high levels of interobserver and intraobserver agreement for the interpretation of CTP in acute stroke, particularly of mean transit time, delay time, and penumbra maps. Abstract : Supplemental Digital Content is available in the text.